PTH-004 Video Capsule Colonoscopy in Routine Clinical Practice. (17th August 2016) - Toth, E; Nemeth, A; Wurm Johansson, G; Koulaouzidis, A; Thorlacius, H
Abstract : Introduction: Colonoscopy is the gold standard in the work-up of patients(pts) with suspected colon pathology. However, conventional colonoscopy is an invasive procedure, associated with certain risks/adverse events and/or occasionally contraindicated. We report routine clinical experience with videocapsule colonoscopy(VCC), in pts with suspected colon pathology, from a tertiary referral centre in Sweden. Methods: 77(20 M/57 F) consecutive pts (median age 56;range 15–89 yrs) with suspected colon pathology were included. PillCam®COLON 1/2 VCC(Given®Imaging Ltd) was used. Bowel preparation advised was 1 day of clear liquid diet, followed by a split-dose administration of polyethylene glycol (3+1 L); in order to enhance gastric & small-bowel transit(SBT) and maximise mucosal visualisation, domperidone(40 mg) and/or on-demand sodium phosphate(30+15 ml) and bisacodyl(10 mg) suppository were administered. Results: Reasons for VCC were previously incomplete and/or declined colonoscopy in 39 & 26 pts, respectively; clinical indications were GI bleeding:28 (36%); suspected inflammatory bowel disease(IBD) or followup in patients with known IBD:23 (30%); and other (colorectal cancer screening, follow up of abnormal radiology & diverticulitis):26 (34%) pts. 58/77 pts (75%) underwent a complete examination of the colon (median colon transit time was 257; range 3–895 min). In 3 cases the capsule did not reach the colon due to stomach retention, small-bowel (stricture) retention & slow SBT. In the remaining 16 incomplete cases the capsule reached the rectum (n = 4), sigmoid (n = 6), descending (n = 5) and transverse colon (n = 1). Good or excellent bowel preparation was achieved in 58 (75%) pts. The most frequent findings were diverticulosis (29 pts, 38%); polyps (17 pts, 22%; size 3–20 mm); active IBD (12 pts, 16%); haemorrhoids (8 pts, 10%); angioectasia (4 pts, 5%) & advance cancer (1 pt, 1%). 15 (19%) pts had no observable colon pathology. Pathological changes in the small-bowel were detected in 8 (10%) pts, including stricture, angioectasia, tumour & Crohn's lesions. All patients tolerated the bowel preparation and the VCC well. Two patients with significant pathology (ulcerated small-bowel stricture and colonic cancer) experienced a temporary capsule retention with spontaneous resolution. Conclusion: VCC is an effective and well-tolerated method to examine the colon. Although further technical development may be needed to examine the whole colon in large numbers of patients, VCC may complement or even replace conventional colonoscopy for certain clinical indications. References: 1 Spada C, et al . Second-generation PillCam® Colon Capsule Compared with Colonoscopy. GIE. 2011;74 :581–9 2 Spada C, et al . Colon capsule endoscopy: ESGE Guideline. Endoscopy. 2012;44 :527–36 Disclosure of Interest: None Declared